2015
DOI: 10.1042/bst20150071
|View full text |Cite
|
Sign up to set email alerts
|

The role of chordin fragments generated by partial tolloid cleavage in regulating BMP activity

Abstract: Chordin-mediated regulation of bone morphogenetic protein (BMP) family growth factors is essential in early embryogenesis and adult homoeostasis. Chordin binds to BMPs through cysteine-rich von Willebrand factor type C (vWC) homology domains and blocks them from interacting with their cell surface receptors. These domains also self-associate and enable chordin to target related proteins to fine-tune BMP regulation. The chordin–BMP inhibitory complex is strengthened by the secreted glycoprotein twisted gastrula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
(44 reference statements)
1
14
0
Order By: Relevance
“…Moreover we show that Tsg interacts with partially cleaved chordin to increase BMP inhibition and promote further cleavage by tolloids. These findings support the physiological relevance of partially cleaved chordin as an important BMP regulator [19]. Our results point to a monomeric Tsg interacting directly with chordin or BMP and suggest that Tsg has a type-specific regulation of BMPs enabling finely controlled regulation of BMP signalling in conjunction with other regulators.…”
Section: Introductionsupporting
confidence: 83%
“…Moreover we show that Tsg interacts with partially cleaved chordin to increase BMP inhibition and promote further cleavage by tolloids. These findings support the physiological relevance of partially cleaved chordin as an important BMP regulator [19]. Our results point to a monomeric Tsg interacting directly with chordin or BMP and suggest that Tsg has a type-specific regulation of BMPs enabling finely controlled regulation of BMP signalling in conjunction with other regulators.…”
Section: Introductionsupporting
confidence: 83%
“…In this study, COL10A1 is likely to influence deposition of the other ECM proteins in the early stage after the application of mechanical stretch. Chordin, a bone morphogenetic protein (BMP) antagonist that binds to BMPs and blocks their interaction with receptors , was also upregulated at 6 h and downregulated at 12 and 24 h of stretch. Chordin is a negative regulator of endochondral ossification in embryonic sternal chondrocytes ; also, chordin can inhibit osteoblast differentiation and mineralization by regulating BMP signaling .…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing the position of the putative Sog glycosylation sites one might gain insight to explain how glycan addition may modify Sog binding to interacting partners. It has been suggested that Chordin and Sog assume a horseshoe-like conformation that enables cooperative BMP binding (Troilo et al, 2015;Larraín et al, 2000;Shimmi et al, 2005). In this arrangement, specific N-and C-terminal regions interact with BMPs (CR1, CR3 and CR4) (Sawala et al, 2012;Troilo et al, 2015), Tsg proteins (CR1 and surrounding) (Yu et al, 2004), heparan sulfate proteoglycans (CR1 and CR4) (Jasuja et al, 2004), integrin receptors (N-terminal) (Araujo et al, 2003;Larraín et al, 2000) and collagen (CR1 and CR4) (Sawala et al, 2012) (Fig.…”
Section: Discussion N-linked Glycosylation Modulates Sog Functionmentioning
confidence: 99%